تاثير تدريبات بالاثقال لتحقيق التوازن عضلي للذراع المفضلة و دقة الاداء المهارة الضربة رافعة (اللولبية) بوجه المضرب الخلفي لتنس الطاولة - رشيد, م. مه به ست أسود; خضر, م.م. أرام كريم; احمد, م.م جيهان محمد (Sulaimani Journal for Humanities, 2023)
Research aims: - Identifying the effect of free weight training on developing muscular balance in the research sample. - Identifying the extent of the effect of exercises on developing the skillful performance accuracy of the research sample. - Recognizing the difference between physical tests and management accuracy, the skill of hitting the screw lever in the face of the back racket in table tennis in the research sample. Research hypotheses: - There is a positive effect of free weight training to achieve muscle balance and accuracy of performance. The human field: the national team players for table tennis for the category (17) years in the Koya Sports Club. Time range: 25/12/2021_3/6/2022. Plase : the inner hall - in the Koya Sport and Youth Center. Conclusions : The weight training used by the researchers in the training program had a positive effect in the development of the accuracy of the performance of the curling strike with the back of the racket. The weight training exercises that the researchers used in the training program had a positive effect in developing the strength and speed characteristic of the two arms clearly. The effect of the training program for developing strength characterized by speed on the muscles (biceps) and muscles (triceps). Recommendations: 1- Using weight training in training all other categories to raise the skill and physical level. 2- Ensuring the scientific basis for the establishment of the training program, especially weight training. 3- Conducting research and other studies and on the skills of math in sports, table tennis.
Keywords: مفتاح الكلمات ( التوازن عضلي الضربة رافعة (اللولبية) )